Trusted digital rights management protocol supporting for time and space constraint - MA Zhao-feng1; FAN Ke-feng2; CHEN Ming1; YANG Yi-xian1; NIU Xin-xin1 (Tongxin xuebao)
A new content protection secure digital right management protocol was proposed,in which content object（CO） and rights object（RO） were separated respectively,and the CO was encrypted by content encryption key（CEK）,while RO was encapsulated by end user’s device related key（DEK）.As for the authentication,dynamical key agreement and authentication protocols was developed for users’ and license centers’ trust management.The proposed CPSec DRM protocol provided personalized and protected license management according to each end user’s location and physical characters,thus it can prevent the license being illegally copied and spread,considering offline license management,a license transfer mechanism was adopted for sub-licenses redistribution.Security analysis manifests the proposed CPSec DRM protocol is secure,reliable and efficient for content protection,authentication,and license management which does not only support online licensing but is feasible for offline license redistribution.